EVALUASI AKSESIBILITAS BAGI TUNANETRA DI PLAZA TRANSIT STASIUN TANAH ABANG - Bonita, Tamara; L. Lukman, Aldyfra (Jurnal Riset Arsitektur, 2022)
Abstract - Visual impairment is a term given to someone who does not have healthy vision. To fulfill their daily life needs, people with visual impairment tend to depend on the facilities in public open spaces. Accessibility that should support people with visual impairment in using public transportation facilities is often poorly maintained. This kind of condition could lead to fatal consequences to the safety of persons with disabilities. Options linked to accessing public open spaces for people with visual impairment become limited due to the lack of facilities. The refurbishment has been done at Tanah Abang Station by providing a transit plaza for users that is connected to various public transportation facilities, which enables easy and comfortable navigation. This has become an opportunity, to build better public facilities that are accessible to all users, including for people with visual impairment. Through this effort, the transit plaza should be able to serve as a public space that is beneficial for people with visual impairment, so there are more possibilities to ensure their quality of life. The purpose of this study is to determine the extent to which the transit plaza can provide accessibility for people with visual impairment. The method used is qualitative and data collection was carried out through literature studies, field surveys as well as interviews and simulations with people with visual impairment. The results conclude that the accessibility value referring to technical requirements indicates that the transit plaza sufficiently complies with accessibility standards regarding public open spaces. This value is compared to the experience of people with visual impairment . This study found that there are some differences from the aspect of convenience according to the people with visual impairment's point of view. The mobility in the transit plaza is considered easy and safe by people with visual impairment. When they had to determine direction or orientation, people with visual impairment who were not familiar with transit plaza still had difficulties to navigate independently. When facing these situations, blind people adapted by relying on abilities other than their sight as an alternative. Transit plaza could provide universal convenience for users by accommodate accessibility that can not only encourage the independence of the people with visual impairment, but also support comfort and safety of individuals without visual impairment. Keywords: Visual impairment, accessibility, transit plaza